High school circa '65 - De los Reyes, Maryo J.; Castillo, Bernardo S.; Salinas, Francisco C.; Tordesillas, Jake.; Agrix Films
The unity of a high school senior class is threatened by gossip about an affair between a respected biology teacher and a popular young new teacher.
Story by Tom Adrales.
Eddie Rodriguez, Liza Lorena, Azenith Briones, Charo Santos.